Human settlements and planning for ecological sustainability : the case of Mexico City - Pezzoli, Keith (Urban and industrial environments., 1998)
In many areas of the world, environmental degradation in and around human settlements is undermining prospects for both socioeconomic justice and ecological sustainability. To explore the issues involved in this worldwide problem, Keith Pezzoli focuses on a dramatic instance of conflict that grew out of the unauthorized penetration of human settlements into the Ajusco greenbelt zone, a vital part of Mexico City's ecological reserve. The Mexican government's initial response to these "irregular" human settlements was contradictory and reactive. Social unrest, ecological deterioration, and violence have all been part of the continuing crisis. The heart of the book is the story of what happened when residents of Los Belvederes, a group of Ajusco settlements, fought relocation by proposing that Los Belvederes be transformed into Colonias Ecologicas Productivas, or productive ecology settlements. Through innovative organized resistance, their grassroots movement generated environmental and social action that eventually won crucial state support. Pezzoli draws upon urban and regional planning theory and practice to examine biophysical as well as ethical and social sides of the story, and he uses the Mexican experience to identify planning strategies to link economy, ecology, and community in sustainable development. -- Provided by publisher.